Evaluation of Our Arabic Language textbook for the fourth grade from the point of view of Arabic language teachers in Mafraq educational directorate in Jordan - Abo Rodiah, Awad Khalaf (Journal of Educational and Psychological Sciences, 2020)
This study aimed to Evaluate Our Arabic Language textbook for the fourth grade from the point of view of Arabic language teachers in Jordan. To achieve the objectives of the study, the researcher developed a questionnaire in five areas: the introduction of the book, the objectives of the book, educational content, teaching aids, methods and activities, and evaluation, and the number of paragraphs of the five areas (55) paragraph. The study consisted of (135) male and female teachers studying our Arabic language textbook for the fourth grade in the Directorate of Education of Qasaba Al- Mafraq Brigade in the academic year (2019/2020). The results of the study showed in the first question in the total degree at the middle level, The mean for the instrument as a whole was (3.62), while the results of the study in the second question showed the existence of statistical differences attributable to the impact of sex and educational qualification in all fields and in the total degree and the benefit of females and graduate studies, and the absence of significant differences due to the impact of years of experience The differences were in favor of 10 years and more.